The Virtual Geometry Model - Hřivnáčová Ivana (EPJ Web of Conferences, 2020)
The Virtual Geometry Model (VGM) is a geometry conversion tool, providing conversion between Geant4 and ROOT TGeo geometry models. Its design allows inclusion of another geometry model by implementing a single sub-module instead of writing bilateral converters for all already supported models. In this presentation we will give an update on the tool architecture, implementation and supported features, the user examples, testing and documentation. We will discuss the opportunities for using the tool for verification of the user geometries. Finally, we will also present the tool build system, distribution and releases policy.